Carbonation Depth of Sustainable Concrete Made with Agroindustrial and Industrial Waste Exposed to the Urban Environment of the City of Xalapa, Ver; Mexico - Baltazar García, Brenda Paola; Baltazar Zamora, Daniel Francisco; Sánchez Sánchez, Odilón; Balderas, Patricia; Mendoza Rangel, José Manuel; Gaona Tiburcio, Citlalli; Landa Ruiz, Laura; Reyes, José; Lozano, David; Méndez, Ce Tochtli; Baltazar Zamora, Miguel Ángel (2023)
In the present investigation the effect of the urban environment of the city of Xalapa, Ver., México in the depth carbonation in Sustainable Concrete made with Agro-Industrial and Industrial Waste Materials like Sugar Cane Bagasse Ash (SCBA) and Silica Fume (SF), was evaluated. The Sustainable Concretes and the Conventional Concrete (Concrete of reference) were designed for a relation water/cement= 0.65 according to the indicated for the ACI 211.1. The Conventional Concrete was elaborated with 100% of Portland cement, and the Sustainable Concretes with partial substitution of Portland cement for the waste of SCBA and SF in percentages of 10, 20, 30, 40, and 50%. The results through the application of phenolphthalein, indicate that the Carbonation depth is proportional to the increase of the substitution of Portland Cement for agro-industrial and industrial waste. The sustainable concrete with 50% of substitution of SCBA-SF presents the worst performance, with a carbonation depth of 1.48 cm, which represents an increment of more of 350% than the conventional concrete at being exposed for one year to the present environment of study